Dairy Propionibacteria: Probiotic Properties and Their Molecular Bases - Franca Rossi; Serena Santonicola; Valerio Giaccone; Alessandro Truant; Giampaolo Colavita (Biomolecules)
This review summarizes the current knowledge on the probiotic characteristics of dairy propionibacteria, represented by Propionibacterium freudenreichii and some Acidipropionibacterium species commonly consumed through raw milk cheese. For example, in Swiss-type cheeses, P. freudenreichii is added as a starter culture. Some strains of P. freudenreichii have been included in mixed probiotic commercial preparations or used to produce tablets from fermented culture media containing bioactive substances such as short-chain fatty acids (SCFAs), bifidogenic molecules, and vitamins. Acidipropionibacterium acidipropionici and A. jensenii strains have mainly been evaluated as health and productivity promoters in farm animals. For P. freudenreichii, the molecular mechanisms behind its probiotic action have been well elucidated, and recently, novel potential applications have been demonstrated in animal models. P. freudenreichii strains have been shown to mitigate inflammatory bowel diseases (IBDs) and mucositis and prevent necrotizing enterocolitis (NEC) in newborns. Their immunomodulation capacity has alleviated symptoms of food allergies, obesity, diabetes, colorectal cancer (CRC), and infections. Moreover, P. freudenreichii inhibited osteoclastogenesis in a rheumatoid arthritis model. Most observed effects are mediated by proteins on the cell surface or contained in extracellular vesicles (EVs) such as the surface layer (S-layer) protein SlpB, DlaT, and GroEL. No safety issues have been reported for these bacteria. However, investigations into transferable antibiotic resistance traits are still needed, and clinical trials are required to evaluate their effectiveness as probiotics for humans.